Studi Kelayakan Bisnis pada UMKM Rempeyek 4 Sekawan : Strategi Analisis SWOT - Erlangga Aditya Pratama; Sinta Sukmawati; Putri Mahabbatun Aliyah; Maisya Hayina Zahra; Perwito Perwito (JURNAL RISET MANAJEMEN (JURMA), 2025)
In the era of globalization, strong economic development is a priority for every country, with a significant focus on the role of Micro, Small, and Medium Enterprises (MSMEs). Using a qualitative descriptive approach of the field research method through interviews by utilizing field research to evaluate Rempeyek's business feasibility study. This research highlights the fundamental contribution of MSMEs to the national economy, especially in addressing issues such as poverty, unemployment, and income distribution. The study emphasizes the importance of understanding market opportunities and capitalizing on them through innovative product offerings that appeal to consumers. One of these promising businesses is the culinary business "Rempeyek 4 Sekawan", a traditional Indonesian snack that has gained popularity in various demographics. The study identified the potential market for reampeyek businesses, especially with the increasing demand for local snacks that combine traditional flavors with modern innovations. However, dynamic market conditions present challenges that require a comprehensive feasibility analysis. Therefore, the results of the research on the 4 friends business are worthy of being carried out as a business opportunity by using analysis that covers various aspects, including market and marketing, finance, operations, production and technology, human resources, and legal considerations. By applying a SWOT analysis, this study aims to provide insight into the competitive position of Rempeyek 4 Sekawan's business, ensuring its sustainability and success in the market.